2020
DOI: 10.1136/lupus-2020-000396
|View full text |Cite
|
Sign up to set email alerts
|

Thoughts on COVID-19 and autoimmune diseases

Abstract: Over the 2 months since coronavirus first appeared in China, cases have emerged on every continent, and it is clear that patients with autoimmune diseases might also be affected. Coronavirus disease 2019 (COVID-19) is a highly contagious viral illness with a mortality rate approaching 2%. Here we discuss the challenges that patients with autoimmune diseases might face and the information on using immunomodulatory therapies like chloroquine, tocilizumab and baricitinib to quench the cytokine storm in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…In a literature review, Favalli et al [11], hypothesized a two-way association between rheumatoid arthritis (RA) and COVID-19: microorganisms can indeed produce acute and chronic arthritis through direct colonisation of the joints or inducing an autoimmune response to the infection. At the same time, an increase in risk of infection in RA subjects compared to the general population due to the impairment of the immune system typical of autoimmune disorders is well documented: Askanase et al [12] pointed out a lack of knowledge in the COVID-related respiratory complications in subjects with autoimmune diseases, in particular for SLE subjects that may be susceptible to the more severe manifestations of COVID-19, such as pneumonia. They even suggested that high type I interferon levels, found clustered in SLE families [13], may exert, on the contrary, a protective effect on COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In a literature review, Favalli et al [11], hypothesized a two-way association between rheumatoid arthritis (RA) and COVID-19: microorganisms can indeed produce acute and chronic arthritis through direct colonisation of the joints or inducing an autoimmune response to the infection. At the same time, an increase in risk of infection in RA subjects compared to the general population due to the impairment of the immune system typical of autoimmune disorders is well documented: Askanase et al [12] pointed out a lack of knowledge in the COVID-related respiratory complications in subjects with autoimmune diseases, in particular for SLE subjects that may be susceptible to the more severe manifestations of COVID-19, such as pneumonia. They even suggested that high type I interferon levels, found clustered in SLE families [13], may exert, on the contrary, a protective effect on COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As a life-threatening condition, most of the research has primarily focused on the respiratory system for survival rate improvement, leaving the effects on other systems or districts still unclear or unknown. [4][5][6][7] Regarding eye involvement in COVID -19, only few data are currently available. 8 The subfamily of Orthocoronavirinae -in which SARS-CoVs belong to the Betacoronavirus genusis already known to occasionally affect ocular structures.…”
Section: Introductionmentioning
confidence: 99%
“…They can suffer from comorbidity like chronic kidney disease and obesity and consequently have more severe forms of COVID-19 [66,67]. Recently, the ACR advise patients with SLE to talk to their rheumatologist and follow recommendations before the interruption of the therapy during SARS-CoV-2 infection [50,68] However, there are no current specific advice and therapeutic strategy for patients with SLE.…”
Section: Recommendations For Patients With Rheumatic Diseases and Covmentioning
confidence: 99%